Dampak Liberalisasi Pemikiran Islam terhadap Kehidupan Sosial - Mujahid Imaduddin (Universitas Darussalam Gontor, 2017)
This paper will research the meaning of the liberalization of religious thought which can not be separated from the history of modern Western civilization and postmodern. Trends of liberalism has begun from individual liberation efforts in economics and politics, then spread to the individual liberation in intellectuality, religious field, and many other fields. Liberalization of thought goes into Islam through several methods and approaches. Some of them are relativism of truth, reinterpretation of the Koran, and deconstruction of Syariah. Through the program, pluralism ultimately has a negative impact on social life. The impact can be seen in Syariah field like allowing interfaith marriage. While in aqidah it is like acknowledging the right faith of other religions, and in morals it is like relativization of good and bad standard in people by ignoring the role of religion. It is becoming worse when the program is not only propagated by the orientalists, but also spread by some Indonesian Muslim scholars. As a result, it is not a surprise if some scientific studies in Indonesia, that can be found in books, magazines or journals which carried articles supporting liberalism movement of Islamic thought. Looking at the urgency of liberalization of Islamic thought issue, this theme should be researched comprehensively. This paper will focus on a discussion of researching programs of liberalization of religious thought, which could affect people social life. The impact has been devastating in a small institution of society, the family.